Pristine, metal ion and metal cluster modified conjugated triazine frameworks as electrocatalysts for hydrogen evolution reaction. Issue 16 (12th April 2021) - Zhang, Boying; Zhang, Yunrui; Hou, Meiling; Wang, Wenbo; Hu, Shuozhen; Cen, Wanglai; Cao, Xuepu; Qiao, Shanlin; Han, Bao-Hang
Abstract : Two covalent triazine frameworks with homoporous and heteroporous structures were modified with metal ions and metal clusters. Their electrocatalytic hydrogen evolution reaction exhibits good performance with low overpotential and small Tafel slope. Abstract : Two-dimensional covalent triazine frameworks (2D-CTFs) are N-rich conjugated porous polymers in which high porosity, adjustable electronic property, and abundant active sites are advantageous to electrochemical water-splitting. Herein, we synthesize two crystalline 2D-CTFs with different pore sizes, namely BPY-CTF with single-sized pores and DCP-CTF with heteropores. Via the confinement effect of porous structure, metal ions (copper, cobalt, nickel, palladium, and platinum) and their corresponding nanoscale metal clusters are inserted into bulk CTFs as catalytically active sites to improve the catalytic activity for water-splitting. The as-synthesized CTFs, CTF-M 2+, and CTF@MC were evaluated as HER catalysts in acidic solution. The symbiotic DCP-CTF-Pt 2+ demonstrated a remarkable electrocatalytic performance, with an overpotential of 46 mV and a Tafel slope of 30.2 mV dec −1, comparable to those of commercial 20% Pt/C. Furthermore, we employed the Vienna ab initio simulation package (VASP) with the projector augmented wave method to conduct first principle calculations to reveal the electrocatalytic activity, which indicated that the excellent catalytic activity of DCP-CTF-Pt 2+ arises from the synergetic effect of intrinsic porosity and adjacent double N anchor sites, which coordinate metal ions, sharply increasing the catalytic kinetics and stability of HER.